(untitled) (Web of Teachers: Inderscience Research, 2024)
Today, it is an important issue to transfer linguistic models and speech capabilities of natural language to computer language and to solve language-related issues with the help of information technologies and methods. The stability of development of all languages in the information age, preservation of their national purity is one of the global problems. In the era of rapid development of computer technologies, interdisciplinary cooperation is important for the development of every science.